Compliance with school nutrition policies in Ontario and Alberta: An assessment of secondary school vending machine data from the COMPASS study - Vine, Michelle M. (Can J Public Health, 2017)
OBJECTIVES: We investigated the extent to which a sample of Ontario and Alberta secondary schools are being compliant with their respective provincial nutrition policies, in terms of the food and beverages sold in vending machines. METHODS: This observational study used objective data on drinks and snacks from vending machines, collected over three years of the COMPASS study (2012/2013–2014/2015 school years). Drink (e.g., sugar-containing carbonated/non-carbonated soft drinks, sports drinks, etc.) and snack (e.g., chips, crackers, etc.) data were coded by number of units available, price, and location of vending machine(s) in the school. Univariate and bivariate analyses were undertaken using R version 3.2.3. In order to assess policy compliancy over time, nutritional information of products in vending machines was compared to nutrition standards set out in P/PM 150 in Ontario, and those set out in the Alberta Nutrition Guidelines for Children and Youth (2012) in Alberta. RESULTS: Results reveal a decline over time in the proportion of schools selling sugar-containing carbonated soft drinks (9% in 2012/2013 vs. 3% in 2014/2015), crackers (26% vs. 17%) and cake products (12% vs. 5%) in vending machines, and inconsistent changes in the proportion selling chips (53%, 67% and 65% over the three school years). Conversely, results highlight increases in the proportion of vending machines selling chocolate bars (7% vs. 13%) and cookies (21% vs. 40%) between the 2012/2013 and 2014/2015 school years. CONCLUSION: Nutritional standard policies were not adhered to in the majority of schools with respect to vending machines. There is a need for investment in formal monitoring and evaluation of school policies, and the provision of information and tools to support nutrition policy implementation.